Dinosaurs Before Dark - Osborne, Mary Pope; Illustrated by Murdocca, Sal (New York Random House, 1992)
Eight-year-old Jack and his younger sister Annie find a magic treehouse, which whisks them back to an ancient time zone where they see live dinosaurs.
"A First stepping stone book."
Keywords: Dinosaurs; Time travel; Magic; Tree houses